2001
DOI: 10.1039/b102427m
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium between neutral hexacoordinate silicon complexes and ionic pentacoordinate siliconium salts through fast dissociation–recombination of the Si–Cl bond

Abstract: Equilibrium between neutral hexacoordinate silicon complexes and ionic siliconium chlorides, which is highly temperature, solvent, counterion, ligand and substituent dependent, was observed by low temperature 29 Si NMR and confirmed by crystal analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…At higher temperatures the signal is shifted to higher field (e.g., δ =−111.2 ppm at 316 K). This counter‐intuitive temperature dependence (ionic dissociation upon cooling) has already been reported by Kost et al 3b. for complexes of the type ( O,N ) 2 SiPhCl (where ( O,N ) is a mono‐anionic hydrazide‐derived chelating ligand), and can be attributed to better anion solvation at lower temperatures.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…At higher temperatures the signal is shifted to higher field (e.g., δ =−111.2 ppm at 316 K). This counter‐intuitive temperature dependence (ionic dissociation upon cooling) has already been reported by Kost et al 3b. for complexes of the type ( O,N ) 2 SiPhCl (where ( O,N ) is a mono‐anionic hydrazide‐derived chelating ligand), and can be attributed to better anion solvation at lower temperatures.…”
Section: Resultssupporting
confidence: 63%
“…In the course of our investigations, we have studied silicon complexes with bi‐, tri‐, and tetradentate O , N ‐donor ligands,3b,c,f, 4a,b, 6 silicon complexes with five‐membered N ‐heterocyclic donor moieties,2g, h, 7 and other silicon compounds of pyrrole‐derived ligand systems 8. In the work reported herein, we now address silicon complexes with pyrrole‐functionalized bidentate O , N ‐chelating ligands.…”
Section: Introductionmentioning
confidence: 99%
“…To a solution of 0.8 g (2.2 mmol) of 7a in acetonitrile was added 0.85 g (4.3 mmol) of CF 3 SO 3 SiMe 3 . The reaction was boiled to reflux for 8 h and then cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This occurs via an equilibrium for which there is a dramatic shift towards loss of Cl Ϫ as the temperature decreases. 174 It is suggested that the mechanism for the process might involve increasing solvent reorganisation around the ions or strengthening of the Si-N bond.…”
Section: -Co-ordinationmentioning
confidence: 99%